Quand le droit au logement disparaît-il ? - Charlie Lorius (Terrains/Théories)
Although it’s one of the rights cited by the 1948 Universal Declaration, access to housing and its impact one other rights is a constant problem for public assistance. The aim of the article will be to use the Declaration as a paradigm to identify the obstacles posed to the emergency accommodation of non-EU foreign families in France. The study mobilises methods of comprehensive sociology, and proposes to analyse the practices of public authorities with legal and moral concepts such as rights and obligations. The results show confusion resulting from the assimilation of people and institutions. The article concludes that there is a correlation between the power of institutions, the freedom of professionals and the lack of rights of peoples.